Noncontiguous finished genome sequence and description of Necropsobacter massiliensis sp. nov. (November 2015) - Lo, C.I.; Padhamanabhan, R.; Fall, B.; Sambe-Ba, B.; Mediannikov, O.; Nguyen, T.-T.; Prudent, E.; Faye, N.; Wade, B.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Strain FF6 T was isolated from the cervical abscess of a 4-year-old Senegalese boy, in Dakar, Senegal. MALDI-TOF MS did not provide any identification. This strain exhibited a 95.17% 16S rRNA sequence identity with Necropsobacter rosorum . Using a polyphasic study including phenotypic and genomic analyses, strain FF6 T was an aero-anaerobic Gram-negative cocobacillus, oxidase positive, and exhibited a genome of 2, 493, 927 bp (1 chromosome but no plasmid) with a G+C content of 46.2% that coded 2, 309 protein-coding and 53 RNA genes. On the basis of these data, we propose the creation of Necropsobacter massiliensis sp. nov.